The Effect of Warm Breast Compresses on Breast Milk Flow in Postpartum Mothers at Lala Medicare Clinic - Ayu Kurnia Anggraeni; Antika Maulida Rahayu (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Breast milk is the optimal source of nutrition for infants; however, many postpartum mothers experience inadequate breast milk flow during the early postpartum period. One non-pharmacological intervention that may support lactation is the application of warm breast compresses, which can stimulate milk ejection and improve blood circulation. This study aimed to examine the effect of warm breast compresses on breast milk flow in postpartum mothers at Lala Medicare Clinic. Methods: This quantitative study employed a quasi-experimental one-group pretest–posttest design. A total of 30 postpartum mothers were selected using total sampling. Breast milk flow was assessed before and after the intervention. Warm breast compresses were applied at a temperature of 40–45°C for 15–20 minutes according to standard procedures. Data were analyzed using the Wilcoxon Signed Rank Test. Results: The proportion of mothers with adequate breast milk flow increased from 26.7% before the intervention to 66.7% after the intervention, while those with inadequate flow decreased from 33.3% to 6.6%. Statistical analysis showed a significant difference in breast milk flow before and after the intervention (p = 0.001). Conclusions: There is an effect of warm compress application on breast milk flow in postpartum mothers.